Association between waist-to-height ratio and stroke among American adults: National Health and Nutrition Examination Survey 1999–2023 - Yahui Pan; Yanzhen Sun; Xiaohua Pan (Discover Public Health)
Abstract Background The waist-to-height ratio (WHtR) is a simple and effective tool for assessing central obesity. However, few studies have investigated the relationship between WHtR and the risk of stroke among US adults. This study aimed to explore the association between WHtR and stroke. Methods We analyzed data from individuals over 20 years of age who participated in the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2023, focusing on their stroke, WHtR, and several other essential variables. Data from NHANES were utilized to explore the association between WHtR and stroke. WHtR was calculated from measured waist circumference and height. The diagnosis of stroke was determined using self-reported data from the survey questionnaire. The primary analytical methods employed in this study included multivariable logistic regression, stratified analysis with interaction, restricted cubic splines (RCS) to investigate the association between WHtR and stroke among American adults. Results There were 43,278 participants, with 1,599 (3.7%) who were identified with stroke. Multivariate regression analysis demonstrated a significant positive correlation between WHtR and stroke risk. For each one-unit increase in WHtR, the risk of stroke increased by 8% (95%CI 1.16–3.75, P = 0.015). When WHtR was categorized into quartiles, the unadjusted model revealed that the risk of stroke in the highest quartile Q4 (≥ 0.654) was increased compared to the lowest quartile Q1 (≤ 0.525), with an odds ratio 3.01 (95% CI: 2.56–3.54, P < 0.001). In the fully adjusted model, the increased risk of stroke in Q4 (≥ 0.654) relative to Q1(≤ 0.525) remained significant, with an odds ratio 1.22 (95% CI: 1.03–1.46, P = 0.025). Accordingly, there was a positive correlation between WHtR and stroke in RCS (P = 0.925) in RCS. Conclusion This study demonstrates a positive linear relationship between WHtR and the risk of stroke, suggesting potential implications for stroke prevention and treatment. Future prospective cohort studies will delve into this association to uncover the mechanisms at play.